Implicações das propriedades estruturais de redes para o gerenciamento de projetos interorganizacionais de geração de energia eólica - Adami, Vivian Sebben (Universidade do Vale do Rio dos Sinos, 2015)
One of the priorities of sustainable world agenda is promoting the use of renewable energy sources, like wind power. The growth of this source developed an industry in Europe and in the United States to supply the demand of these precursors markets. Recently (in the last decade), Brazil along with China and India has been investing in wind generation and emerging on the world scenario. The deployment of wind farms happens through inter-organizational projects (IOPs), involving shared activities among companies with different interests and capabilities in an environment of risks and uncertainties. This research aims to contribute to the still new topic of the wind industry IOPs, having support in recent progress of knowledge on networks and structural properties. Its main goal is to understand how the characteristics of networks established in the context of wind power generation IOPs affect the development of Brazilian initiatives. Recent studies have adopted social networking perspective for understanding and improving relations in IOPs. In these studies, IOPs are understood as a network of interdependent actors that can be detailed from their structural properties at various levels. Network mapping, analysis and characterization from multiple levels shed light to issues hitherto complex for the development of wind farms. The introduction of the triadic level, still little explored in studies of interorganizational networks, enables new visions to actors structural and positional aspects. The networks are a relatively new phenomenon, and the field of study still resents the lack of research that address the relational structures between the actors. The joint use of quantitative approaches, with the adoption of social network analysis, and qualitative, based on semi-structured interviews, made it possible to incorporate different (and complementary) analysis perspectives to the phenomenon. In academic terms, one of the research contributions was the development of a theoretical framework for the structural properties of IOPs on many levels, reinforcing the explanatory power of the structure over the individual attributes of the actors. Another result was the identification of relations and key roles for structuring more effective management models. Informal relations, invisible in supply and procurement networks, happen within a cooperative logic and are important in coordinating the project. In managerial terms, the contributions focused on understanding the relational structure of the IOPs, their operation, and issues related to the implications of the structural properties to its management. The composition and organization of IOPs was revealed as well as the importance of cooperation or of a relational structure that encourages cooperation between project participants.
Keywords: Projetos interorganizacionais eólicos; Redes; Propriedades estruturais; Tríades; ARS; Interorganizational projects; Structural properties; Triads; SNA; Wind farms; ACCNPQ::Ciências Sociais Aplicadas::Administração